Evaluation of a method to detect Mycobacterium bovis in air samples from infected Eurasian badgers (Meles meles) and their setts. (1st March 2013) - Jones, R.M.; Ashford, R.; Cork, J.; Palmer, S.; Wood, E.; Spyvee, P.; Parks, S.; Bennett, A.; Brewer, J.; Delahay, R.; Chambers, M.; Sawyer, J.
Abstract Environmental air sampling was evaluated as a method to detect the presence of M. bovis in the vicinity of infected badgers and their setts. Airborne particles were collected on gelatine filters using a commercially available air sampling instrument and tested for the presence of M. bovis using bacteriological culture and real‐time PCR. The sensitivity of bacteriological culture was broadly similar to that of real‐time PCR when testing samples artificially spiked with M. bovis. Sampling was undertaken from directly under the muzzles of badgers which had been experimentally infected with M. bovis (37 samples), within enclosures housing the experimentally infected animals (50 samples), and in the vicinity of setts with resident infected wild badgers (52 samples). The methods employed did not detect M. bovis from either infected badgers or artificial or natural setts known to contain infected animals. However, samples taken at four of the six natural setts were positive for Mycobacterium gordonae.